2022
DOI: 10.1098/rsbl.2021.0642
|View full text |Cite
|
Sign up to set email alerts
|

Small, odd and old: The mysteriousTarsius pumilusis the most basal Sulawesi tarsier

Abstract: In this study, we present the first genetic evidence of the phylogenetic position of Tarsius pumilus, the mountain tarsier of Sulawesi, Indonesia . This mysterious primate is the only Eastern tarsier species that occurs exclusively in cloud forests above 1800 m.a.s.l. It exhibits striking morphological peculiarities—most prominently its extremely reduced body size, which led to the common name of ‘pygmy tarsier’. However, our results indicate that T. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…The genus includes T. tarsier Erxleben 1777, T. fuscus Fischer 1804, T. sangirensis Meyer 1897, T. dentatus Miller and Hollister 1921, T. pumilus Miller and Hollister 1921, T. pelengensis Sody 1949, T. lariang Merker and Groves 2006, T. tumpara Shekelle et al 2008, T. wallacei Merker et al 2010, T. spectrumgurskyae Shekelle et al 2017, T. supriatnai Shekelle et al 2017, and T. niemitzi Shekelle et al 2019 (Niemitz et al 1991;Merker and Groves 2006;Shekelle et al 2008;Merker et al 2010;Groves 2012;Shekelle et al 2017Shekelle et al 2019. Based molecular data using autosomal phylogenetic and the SRY gene showed that the Tarsier came to Proto-Sulawesi during the initial Miocene tectonic uplift (Driller et al 2015), with T. pumilus being the basal Tarsier in Sulawesi (Hagemann et al 2022). The conservation status of the Tarsier, especially 12 species of Tarsier in Sulawesi, is categorized as data-deficient to critically endangered (Supriatna 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The genus includes T. tarsier Erxleben 1777, T. fuscus Fischer 1804, T. sangirensis Meyer 1897, T. dentatus Miller and Hollister 1921, T. pumilus Miller and Hollister 1921, T. pelengensis Sody 1949, T. lariang Merker and Groves 2006, T. tumpara Shekelle et al 2008, T. wallacei Merker et al 2010, T. spectrumgurskyae Shekelle et al 2017, T. supriatnai Shekelle et al 2017, and T. niemitzi Shekelle et al 2019 (Niemitz et al 1991;Merker and Groves 2006;Shekelle et al 2008;Merker et al 2010;Groves 2012;Shekelle et al 2017Shekelle et al 2019. Based molecular data using autosomal phylogenetic and the SRY gene showed that the Tarsier came to Proto-Sulawesi during the initial Miocene tectonic uplift (Driller et al 2015), with T. pumilus being the basal Tarsier in Sulawesi (Hagemann et al 2022). The conservation status of the Tarsier, especially 12 species of Tarsier in Sulawesi, is categorized as data-deficient to critically endangered (Supriatna 2022).…”
Section: Introductionmentioning
confidence: 99%